Religions and Beliefs of the Ancient Eurasian Society: A socio anthropological study of a sample of prevailing - Benseghir, Rahima (Journal of Human Sciences, 2023)
This socio anthropological study came within the framework of observing the religions and patterns of beliefs prevailing in the ancient Eurasian society, whith was characterized by the diversity of religions such as Judaism, Christianity and paganism and what appeared from the from the worship of gods and lords, down to religious beliefs and the popular practices that came from them in an attempt to return to understanding the making of the social actor of meaning Religious space in the ancient Aures. The study concluded that the contact of the Auras community with other peoples strengthened the identification of individuals with the religions of others, including Judaism and Arianism, in addition to the historically rooted paganism, and from it the cultural reinforces the religious.